Correction to: Exploring expected and perceived facilitators and barriers of an indicated prevention strategy to prevent future longterm sickness absence; a qualitative study among employers and employees - Sophie H. Klasen; Ludovic G. P. M. van Amelsvoort; Inge Houkes; Nicole W. H. Jansen; IJmert Kant (BMC, 2021)
An amendment to this paper has been published and can be accessed via the original article.